First record of the sea anemone Anthopleura mariscali outside the Galápagos Archipelago - Quesada, Andrés J. (2017)
The sea anemone Anthopleura mariscali Daly and Fautin 2004 is described as an endemic species of the Galápagos Archipelago. Its authors suggested that it may have been overlooked elsewhere because of its small size and because it is usually found inside cracks and crevices. This report presents the first record of A. mariscali outside its type locality. Eight specimens were collected from a rocky promontory in Playa Agujas, Puntarenas, on the Pacific coast of Costa Rica. Analyses of their cnida composition are presented along with images of some live sea anemones.